Pengaruh Magang Pendidikan Terhadap Pengembangan Kompetensi Mahasiswa - Ayunda Putri A. Siregar; Nadya Dinul Qoyyimah; Azizah Surayya; Sahraini Yamni N. F. Nasution; Deasy Yunita Siregar (Politeknik Kampar, 2024)
This study discusses the influence of educational internships on the development of student competencies in the context of higher education. Educational internships are a practical form of learning outside the classroom that provides students with the opportunity to apply their theoretical knowledge in the real world. The aim of this research is to understand the extent to which educational internships contribute to the development of student competencies, including practical skills, analytical abilities, industry understanding, the formation of professional networks, and the cultivation of positive attitudes and work ethics. The results of this study show that educational internships have a significant and positive impact on the development of student competencies. Students who undergo internships experience improvements in practical skills, including interpersonal communication, time management, and problem-solving abilities. They also develop strong analytical skills and gain a deeper understanding of industry dynamics relevant to their field of study. Furthermore, educational internships enable students to build professional networks that can be valuable in their future job searches. Ultimately, internships also play a role in shaping positive attitudes and work ethics. In conclusion, this research underscores the importance of educational internships in helping students prepare for success in the workforce. Institutions of higher education need to recognize their pivotal role in fostering student competency development and collaborate with the business world to provide more relevant and beneficial internship opportunities. Thus, educational internships can be a valuable investment in enhancing students' skills and qualifications.